Farmer’s perception of agrochemical use on honeybees and honey production in Benin: Implication for organic honey production - Dassou, Anicet; Kindomihou, Valentin Missiakô (My University, 2023)
Beekeeping faces numerous challenges, including the use of agrochemicals. Honeybee colonies are lost because of chemical pesticides use in agriculture to control pests and diseases, which affects detoxifying mechanisms and immune responses, making them more vulnerable to parasites. The purpose of this study was to investigate people’s perception of the impact of agricultural pesticide use on the honeybee community and honey production in northern Benin. A survey was conducted using a questionnaire among 100 beekeepers. Individual interviews were used to gather information on treated crops, the distance between beehives and these cultivated fields, the effect of pesticides and herbicides, alternative methods to pesticide use and honey production. Chemical pesticides such as Callifor G, Kalach, Atrazila 80 WP, Herbextra, Atraforce, Adwumawura (480 SL), Cottonex, Thalis, Cotonix and Cypercal P 330 EC were used in agricultural fields, and beehives were typically found near treated fields. The majority of beekeepers (79%) are aware of the risks associated with pesticides and employ non-pesticide alternatives such as biopesticides to minimize them. In general, beekeepers reported a reduction in the big breed of bees and a 40% decrease in the little breed. When the beehives were placed far away from the treated areas, the honey yield was higher. Alternative pest management strategies to farmers' pesticide use would result in long-term increases in honey production and would constitute the main step of the conversion to organic apiculture in northern Benin.
Keywords: Beekeeping; Agrochemicals; Honeybees; Honey production; Benin.